A Black Sticky Rice-Derived Functional Ingredient Improves Anxiety, Depression, and Stress Perception in Adult Volunteers - Pattamaporn Natthee; Jintanaporn Wattanathorn; Wipawee Thukham-mee; Pongsatorn Paholpak; Poonsri Rangseekajee; Nawanant Piyavhatkul; Suphayanakorn Wattanathorn; Supaporn Muchimapura; Terdthai Tong-Un (Foods)
We hypothesized that consumption of a diet containing the functional ingredient from black sticky rice, which is rich in anthocyanin, over a five-day period would improve anxiety, depression, and stress perception in adult volunteers based on the benefits of this compound. In this study, a total of 46 male and female adult volunteers with mild and moderate stress level were assigned to groups consuming a breakfast meal containing an anthocyanin-enriched functional ingredient at doses of 2 and 4 g per day for 5 days. The volunteers consumed three meals with a low DII but high DAQ-S, and the total calories consumed during the study period was 2000 kcal/day. Mental well-being, including depression, anxiety, and stress, together with AChE, MAO, Nrf2, 8OHdG, MDA, and the density of Lactobacillus and Bifidobacterium spp., were assessed at baseline and at the end of the study. Safety parameters were also examined. A diet containing both doses of the anthocyanin-enriched functional ingredient with a low DII but high DAQ-S was found to improve anxiety, depression, and stress, with changes in 8-OHdG and IL-6 levels. No other changes and toxicity-related parameters were observed. Our results show that the novel functional ingredient can improve anxiety, depression, and stress perception partly by decreasing oxidative stress and inflammation; however, randomized, double-blind, placebo-controlled studies with a larger sample size should be performed to confirm this benefit.